Concurrent recording of neurometabolic changes and local field potential in the central nervous system of awake-behaving rodent models of epilepsy. (29th March 2019) - Ledo, Ana; Lourenço, Cátia F.; Laranjinha, João; Gerhardt, Greg A.; Barbosa, Rui M.
Abstract : Introduction: Temporal lobe epilepsy (TLE) is a form of acquired epilepsy characterized as an electro-clinical syndrome in which seizures emanate from the limbic system [1, 2 ]. TLE is particularly disabling due to the unpredictable and recurrent nature of seizures and incidence of antiepileptic drug resistance [3 ] many times an indication for resection surgery [4, 5 ]. Pre-surgical identification of the seizure onset zone relies on multimodal methods based on different pathophysiological principles. The golden standard technique is long-term intracranial electroencephalogram (EEG) [6 ] combined neuroimaging techniques, which explore brain hemodynamics as a surrogate signal for brain activity [7, 8 ]. To date, no single sensor approach allows simultaneous and seamless recording of electrical and hemodynamic responses. Materials and methods: We used multisite ceramic-based Pt microelectrode arrays (MEAs) to perform high-frequency amperometric recording of p O2 and local field potential (LFP)-related currents in the CNS of chronically implanted freely-moving rats during pilocarpine-evoked status epilepticus . Using fast Fourier transform (FFT) filtering of the raw electrochemical signal we separated into the low frequency component (<1 Hz), corresponding to the electrochemical reduction of O2 and high (>1 Hz) frequency component, corresponding to the LFP currents. Results: We determined the mean resting level of p O2 in two subregions of the hippocampus as well as in the striatum and the cortex of freely moving rats. The hippocampal DG showed lowest ( p  < 0.01) resting p O2 level (6.6 ± 0.7 μM) when compared to CA1 (22.1 ± 3.4 μM), striatum (17.2 ± 1.7 μM), and cortex (22.1 ± 4.9 μM). Evoked changes in interstitial p O2 in vivo we performed a 5 min tail pinch stress paradigm test, which induced a transient increase p O2 in the hippocampus of 15 ± 4% from baseline, corresponding to an average Δ[O2 ] of 3.7 ± 0.6 μM. Induction of status epilepticus induced biphasic changes in p O2 in the hippocampus. The initial dip at seizure onset (−4.5 ± 0.7 µM) was followed by a prolonged hyperoxygenation phase (+10.4 ± 2.9 µM). Analysis of high-frequency component of the amperometric signal allowed the simultaneous monitoring LFP at the site of p O2 recording. This has high potential for translation into the clinical setting supported on intracranial grid or strip electrodes. Discussion and conclusions: This strategy revealed that a single sensor can simultaneously report chemical ( p O2 ) and electrophysiological (LFP currents) information, allowing concurrent monitoring of electrical and neurovascular/neurometabolic activities.